The cascade of benzodiazepine prescribing for hospitalized geriatric patients - Neshahthari Wijeyakuhan; Rachel Gruber; Nicholas A. Rattray (Greater Baltimore Medical Center, 2020)
Background Hospitalists increasingly provide care for geriatric patients and little is known about the extent to which hospitalists adhere to evidence-based medication guidelines. This study aimed to characterize hospitalist adherence to BEERS guidelines for prescribing and monitoring benzodiazepines for older adults. Methods We conducted a retrospective chart review of admitted patients aged 70-85 years who had been prescribed benzodiazepine. Charts from 351 patients were analyzed for documentation and decision rationale, which included 638 separate notes. Results Benzodiazepines were prescribed 28.2% of the time to address anxiety, which is inconsistent with the BEERS criteria; 39% had adequate data in the impression and plan section of the note to reflect why benzodiazepine was prescribed. Of note, the majority of notes had partial or missing data. Conclusion Physicians tended to follow guidelines more than advance practice providers. Wide variation persists in prescribing practices and documentation related to benzodiazepines and both could potentially be addressed with further training.